Nursing in the Century XXI: Recovering the dialectic dimension of the construction of social practical one for diverse actors. - Helena Maria Scherlowski Leal David; Iraci dos Santos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This is the Review of Volume 4 of the Series in Nursing Update, published at the beginning of the twenty-first century. The book focuses on the Brazilian Nursing struggle to find their way towards promotion of quality of life for human beings, pursued since his meeting with the professionalization, sent by Florence Nightingale. Emphasizes the professional Nursing practice in Brazil, a country of great cultural and social diversity, which requires relevant and applicable public health policies. It's originality is due to the understanding that Health Care depends on attitudes and behaviors of all health professionals categories and kowledges. Exposes Brazilian nursing remarkable progress in the development of technical actions in health care, in individual and collective level. As a social practice, nursing trajectory is closely linked to the historical health achievements for population.